Translokalitas Budaya Sorkam pada Penggunaan Ruang Untuk Kegiatan Sehari-hari Masyarakat di Perumahan Bumi Yapemas Indah, Bekasi - Aisha, Heidi; Ekomadyo, Agus S. (ARSITEKTURA, 2021)
Indonesia has various ethnic societies that have been migrated from their origin places and settled in other regions. It also occurs where Sorkam community, a coastal ethnic communities originalle placed in Central Tapanuli, North Sumatra, have moved and settled in Bumi Yapemas Indah Housing, South Tambun, Bekasi Regency. This article discusses how specific ethnic communities lives in a modern gated-community in everyday life. It examines how communities using space in everyday lives and and their cultural forms is maintained in translocal living spaces. By Lefebvre’s rhythmanalysis approach, research is conducted with interviews with community leaders and a sample of residents, and also field observation. It is found that the traditional culture of the Sorkam people did not have a direct effect on the architecture and use of space, but the similarity in the culture of the community encouraged the interaction between the rhythms of people's lives. Cultural similarity encourages interaction between the rhythms of people's lives so that the phenomenon of space use is reinforced according to the Eurhythmia concept. The phenomena of using the space include: 1) the emergence of a sense of security and comfort in using spaces 2) utilization of indoor and outdoor spaces as a social space, and 3) adjustment of space according to the culture of the local community. It is hope this article will contribute to the studies of social production of space by specific community.